'If there is a Dream there, Don't Squash it!': School to Life-after-School Transition Experiences of Autistic Youth within Australia's National Disability Insurance Scheme - Huska, Marie; Devine, Alexandra; Naccarella, Lucio (International Journal of Educational and Life Transitions, 2023)
Introduction: Difficulty accessing services and supports during critical life transitions are recognised as contributing to unacceptably poor life outcomes for Autistic Australians. The National Disability Insurance Scheme (NDIS) provides funding for eligible individuals with permanent and significant disability to purchase services and supports to meet their needs and aspirations, holding the potential to improve transition support for the third of all NDIS participants with a primary diagnosis of autism.Aim: This paper reports on research to better understand the NDIS policy and practice environment supporting Autistic youth during transition to life-after-school.Methodology: Using a qualitative approach, individual interviews were completed with four Autistic NDIS participants aged 18–21 in 2019. Separate interviews were conducted with four family members nominated by each of the youth interview participants. Thematic analysis explored how Autistic youth and those who support them, experienced NDIS facilitated transition to life-after-school.Results: Two key themes emerged: 1) Transition journeys: aspirations and experiences, and 2) Navigating the NDIS in pursuit of better transition experiences.Conclusion: The research highlights a cross-sector, person and family-centred approach is needed to address barriers and build systems literacy for the NDIS to better meet the transition requirements of Autistic Australian youth.
Keywords: National Disability Insurance Scheme (NDIS); autism; youth; family; transition to life-after-school; lived experience